Living in a hot city: thermal justice through green open space provision - Ufaira, Rifda; Amir, Sulfikar; Indraprahasta, Galuh Syahbana; Nastiti, Anindrya (Frontiers in Human Dynamics, 2023)
Jakarta's environmental problems, the increasing temperature, and the intensifying urban heat island effect (UHIE) add weight to the deteriorating quality of life in the city. Nevertheless, chronic exposure to heat, especially experienced by inhabitants in tropical cities, receives less attention. It is often seen as a low-onset event that requires no immediate action and is not as noticeable and apparent as other heat events, such as heat waves. This slow-onset environmental hazard disproportionately affects the population in the lower socio-economic condition. With their low access to cooling infrastructure, the disadvantaged people of Jakarta live and work in an environment that is prone to extreme heat exposure. Poor urban planning and design contribute to the intensifying urban heat in Jakarta and exacerbate the impacts of heat among by providing mitigating and managing urban heat in the city. Using the Multiple Stream Framework (MSF) lenses, we analyse how and why the issue of urban heat is currently being prioritised in Jakarta and how the provision of green open space contributes to thermal justice in Jakarta. The issue is examined by analysing urban planning policy through government strategy documents and interviews with key stakeholders.